Pushing the Envelope: The Mysterious Journey Through the Bacterial Secretory Machinery, and Beyond - Troman, Luca A.; Collinson, Ian (Frontiers in Microbiology, 2021)
Gram-negative bacteria are contained by an envelope composed of inner and outer-membranes with the peptidoglycan (PG) layer between them. Protein translocation across the inner membrane for secretion, or insertion into the inner membrane is primarily conducted using the highly conserved, hourglass-shaped channel, SecYEG: the core-complex of the Sec translocon. This transport process is facilitated by interactions with ancillary subcomplex SecDF-YajC (secretion) and YidC (insertion) forming the holo-translocon (HTL). This review recaps the transport process across the inner-membrane and then further explores how delivery and folding into the periplasm or outer-membrane is achieved. It seems very unlikely that proteins are jettisoned into the periplasm and left to their own devices. Indeed, chaperones such as SurA, Skp, DegP are known to play a part in protein folding, quality control and, if necessary degradation. YfgM and PpiD, by their association at the periplasmic surface of the Sec machinery, most probably are also involved in someway. Yet, it is not entirely clear how outer-membrane proteins are smuggled past the proteases and across the PG to the barrel-assembly machinery (BAM) and their final destination. Moreover, how can this be achieved, as is thought, without the input of energy? Recently, we proposed that the Sec and BAM translocons interact with one another, and most likely other factors, to provide a conduit to the periplasm and the outer-membrane. As it happens, numerous other specialized proteins secretion systems also form trans-envelope structures for this very purpose. The direct interaction between components across the envelope raises the prospect of energy coupling from the inner membrane for active transport to the outer-membrane. Indeed, this kind of long-range energy coupling through large inter-membrane assemblies occurs for small molecule import (e.g. nutrient import by the Ton complex) and export (e.g. drug efflux by the AcrAB-TolC complex). This review will consider this hypothetical prospect in the context of outer-membrane protein biogenesis.